Ethik als Steigerungsform von Theologie?: Systematische Rekonstruktion und Kritik eines Strukturprozesses im neuzeitlichen Protestantismus - Atze, Stefan (Theologische Bibliothek Töpelmann, 2008)
This study examines the systematic adoption of modern thought by Protestant theology. It discusses theological models which not only topicalise new age themes on a theological level, but translate them directly into a draft programme. The external characteristic of these positions is the central importance of ethics, which functions as a foundation for theology. It is man, not God, from whom theological thinking emanates. The history of radical models of this kind is traced and they are subjected to critical examination